Coping with Merging and Advanced Market Risks - Xia, Harry (International Journal of Economics and Social Science, 2015)

The Future of Macau Aviation Industry: A Long-Term Plan & Development Strategies - Xia, Harry (University of Saint Joseph, 2015)

Banking efficiency and competition: an empirical research on Macau's banking industry - Lei, Hoi Kin (University of Saint Joseph, 2019)
This research examines the relationship between banking competition and efficiency using relevant data of Macau banking industry from 1999 to 2016. The key finding of this research is to demonstrate a clear causality between competition and efficiency in Macau’s banking industry throughout the study period. The interaction between two vital factors of the banking industry provides a solid empirical evidence for the practitioners and policymakers to make sound decisions accordingly. The most recent data show that there is a wide variation of key operational indicators of different banks in 2016. However, this study finds no evidence that the size of operations in terms of total bank loans would impact banks’ efficiency. Economies of scale or market share doesn’t necessarily bring cost efficiency in Macau’s banking industry
Keywords: Doctorate of Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Analysing Sands China Limited HR practices, discovering the challenges, issues and possible solutions - Im, Hoi Tek (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan for a nursery education school - Wong, Weng Ian (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of avon products,inc - Kiki, Michael Oluwasegun (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Galaxy Entertainment Group (GEG) - Ieong, Si Wan (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Implement performanace pledge in Macao government departments: a case of Macao IACM - Choi, Kuai Hong (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Luxury brand development in Macau - Chio, Lai Teng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Top-down vs. Bottom-up Strategies in Macau Banking Sector - Ieong, Mei Sio (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph